Effect of monsoon on ocean productivity in Aceh waters. Issue 1 (February 2021) - Auliati, A; Haditiar, Y; Wafdan, R; Ikhwan, M; Muhammad, M; Jalil, Z; Chaliluddin, M A; Sugianto, S; Rizal, S
Abstract: Monsoon in Aceh waters is dominated by the northeast and southwest monsoons. Based on previous research, the monsoon affects oceanography and general hydrodynamics in Aceh's waters and its surroundings. This study aimed to see the effect of the monsoon on the abundance of chlorophyll-a in Aceh waters. The data used in this study consisted of wind, sea surface temperature (SST), and chlorophyll-a data obtained from remote sensing observation data. Wind data is obtained from Metop-B ASCAT (Advanced SCATterometer). SST and chlorophyll-a were obtained from Aqua MODIS (Moderate Resolution Imaging Spectroradiometer) level 3 with resolution 4 x 4 km. The results obtained, in February, chlorophyll-a concentrations were higher in the range of 0.7 mg/m 3 - 1.4 mg/m 3, compared to August with lower concentrations ranging from 0.2 mg/m 3 - 0.5 mg/m 3 . It is due to low temperatures in February. Seasonal changes affect the productivity content of chlorophyll-a in the waters.